Valuing ecosystem services : toward better environmental decision-making (National Academies Press, 2005)
"Nutrient recycling, habitat for plants and animals, flood control, and water supply are among the many beneficial services provided by aquatic ecosystems. In making decisions about human activities, such as draining a wetland for a housing development, it is essential to consider both the value of the development and the value of the ecosystem services that could be lost. Despite a growing recognition of the importance of ecosystem services, their value is often overlooked in environmental decision-making. This report identifies methods for assigning economic value to ecosystem services even intangible ones and calls for greater collaboration between ecologists and economists in such efforts."--Publisher's description